2014
DOI: 10.1021/mp400687w
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and Lapatinib Combination Nanomedicine for Treating Resistant Breast Cancer

Abstract: Our objective was to design a polymeric micelle-based doxorubicin and lapatinib combination therapy for treating multidrug resistant (MDR) breast cancers. Poly(ethylene glycol)-block-poly(2-methyl-2-benzoxycarbonylpropylene carbonate) (PEG-PBC) polymers were synthesized for preparing doxorubicin and lapatinib loaded micelles using a film dispersion method. Micelles were characterized by determining critical micelle concentration (CMC), particle size distribution, and drug loading. The anticancer effects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…Lapatinib has also been reported with the ability to inhibit the activity of drug efflux transporters. Based on the amphiphilic poly (ethylene glycol)-block-poly (2-methyl-2-benzoxycarbonylpropylene carbonate) polymers, we developed the DOX micelles and lapatinib micelles, simultaneously, to codeliver DOX and lapatinib in treating multidrug-resistant breast cancer 69 . The results of fluorescence microscopy and flow cytometry showed that coadministration of the DOX micelles and lapatinib micelles can enhance DOX uptake in the MCF-7/ADR cells overexpressing drug efflux transporters but not MCF-7 cells low-expressing drug efflux transporters.…”
Section: Nanotechnology-based Combination Therapymentioning
confidence: 99%
“…Lapatinib has also been reported with the ability to inhibit the activity of drug efflux transporters. Based on the amphiphilic poly (ethylene glycol)-block-poly (2-methyl-2-benzoxycarbonylpropylene carbonate) polymers, we developed the DOX micelles and lapatinib micelles, simultaneously, to codeliver DOX and lapatinib in treating multidrug-resistant breast cancer 69 . The results of fluorescence microscopy and flow cytometry showed that coadministration of the DOX micelles and lapatinib micelles can enhance DOX uptake in the MCF-7/ADR cells overexpressing drug efflux transporters but not MCF-7 cells low-expressing drug efflux transporters.…”
Section: Nanotechnology-based Combination Therapymentioning
confidence: 99%
“…Clinical treatments involving a single drug have proven short-lived due to the emergence of resistant cancer cells. A major strategy for overcoming drug resistance is combination therapy 15 16 17 . Given the effectiveness of PL in cancer cell lines and preclinical mouse models, it remains to be answered if a synergistic effect or enhanced induction of apoptosis can be achieved when PL is combined with another drug.…”
mentioning
confidence: 99%
“…Efforts have been made to apply nanomedicine in cancer treatment to improve the efficiency of anticancer regimens (17,18,34,35). In the present study, SWCNTs were used as the carrier of oxygen, which was expected to increase the sensitivity of cancer cells to chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%